Pengaruh Pelatihan dan Disiplin Kerja Terhadap Kinerja Pegawai Pada Dinas XYZ - Septyandi, Chandra Budhi; Susanto, Eko (Universitas Nusa Putra, 2020)
The background of this research is the decrease in employee performance. The issue should be addressed immediately because the optimal and standardized employee performance is important and can support the achievement of organizational goals. This study aims to determine the effect of training and work discipline on employee performance in the XYZ Office. The object that becomes the unit of analysis in this study were employees of the XYZ Office. The type of research used is descriptive, derivative, and the method used is an explanatory survey with a research sample of all units of analysis (population) that is 145 employees of the XYZ Office. The data analysis technique used is multiple linear regression using SPSS 23.0 computer software. Based on the results of the study can be seen that training and discipline work simultaneously and partially have a positive effect on employee performance.